The Basel Committee on Banking Supervision : a history of the early years, 1974-1997 - Goodhart, C. A. E. (Charles Albert Eric) (Cambridge University Press, 2011)
"The Basel Committee on Banking Supervision (BCBS) sets the guidelines for world-wide regulation of banks. It is the forum for agreeing international regulation on the conduct of banking. Based on special access to the archives of the BCBS and interviews with many of its key players, this book tells the story of the early years of the Committee from its foundation in 1974/5 right through until 1997 - the year that marks the watershed between the Basel I Accord on Capital Adequacy and the start of work on Basel II. In addition, the book covers the Concordat, the Market Risk Amendment, the Core Principles of Banking and all other facets of the work of the BCBS. While the book is primarily a record of the history of the BCBS, it also provides an assessment of its actions and efficacy. It is a major contribution to the historical record on banking supervision"--